EXPLORING WOMEN’S PORTRAYAL AND NARRATIVE ENTANGLEMENT IN DAVID LYNCH’S ‘BLUE VELVET’ (1986): POSTMODERN CINEMATIC ANALYSIS - Billah, Zakiyah Dania (Jurusan Sastra Indonesia, 2024)
This study conducted a concise postmodern cinematic analysis of ‘Blue Velvet’ (1986), directed by David Lynch, focusing on the portrayal of women and their narrative roles. ‘Blue Velvet’ exemplifies postmodern cinema through its subversion of conventional storytelling and exploration of dark undercurrents in suburban America. The analysis delved into the multifaceted depiction of women, examining how Lynch employs the “male gaze” through camera work and narrative structure, reinforcing patriarchal power dynamics. By scrutinizing key scenes, we revealed women often depicted for male viewer gratification. This study provided a new viewpoint on ‘Blue Velvet,’ shedding light on its challenge to cinematic norms and highlighting the interplay of gender, power, and narrative in a postmodern context.